What do insects do? - Canizares, Susan, 1960-; Chanko, Pamela, 1968- (New York : Scholastic, 1998)
Photographs and simple text describe the many things that insects do.
2.0
K-3
Keywords: Insects -- Juvenile literature; Insects; Insects